Improving Students' Learning Interest in Islamic Cultural History Through the Make a Match Cooperative Learning Model in Grade VA of MI Al-Umm: A Classroom Action Research - Azizah Haya Dzakiya; Firda Amalia; Mohamad Hafizh; M Makbul; Zainal Abidin (At-Tathbīq: Journal of Education and Learning, 2026)
Purpose of the Study: This study aims to improve the learning interest of Grade VA students in Islamic Cultural History (SKI) at MI Al-Umm through the implementation of the Make a Match cooperative learning model. The research addresses the persistent problem of low student engagement and participation in SKI learning, examining how a structured, interactive pairing strategy can foster greater enthusiasm, active involvement, and sustained interest in the subject matter. Methodology: This research employs Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted across two cycles with two meetings in each cycle. The participants were 33 Grade VA students at MI Al-Umm. Data were collected through learning-interest questionnaires, observation sheets, documentation, and field notes. Quantitative data were analyzed using percentage techniques, while qualitative data were analyzed descriptively to capture changes in student participation and classroom dynamics throughout the intervention. Main Findings: The implementation of the Make a Match model led to a measurable improvement in students' interest in learning, rising from 69.4% in Cycle I to 80% in Cycle II. Observation results further indicated increased student participation, enthusiasm, and active engagement during learning activities. These findings demonstrate that the collaborative, game-based structure of the Make a Match model effectively stimulates motivation and creates a more participatory learning environment in Islamic Cultural History instruction. Novelty/Originality of this Study: This study provides practical evidence on the application of the Make a Match cooperative learning model in the specific context of Islamic Cultural History (SKI) at the elementary madrasah level, an area that remains underexplored in the existing literature. It offers a replicable, classroom-tested strategy for enhancing student learning interest in religious-historical subjects, providing a foundation for educators seeking active-learning alternatives to conventional, lecture-based SKI instruction.